Development of a portable gamma probe for registration and localization of radiation source, including medical application - Kapliy, O.A.; Kiprich, S.K.; Kovalenko, G.D.; Ovchinnik, V.D.; Shirokopetlev, F.O.; Shlyakhov, I.M.; Shulika, M.Yu.; Vasiliev, G.P.; Yalovenko, V.I. (Problems of Atomic Science and Technology, 2023)
Self-powered portable gamma probe has been developed on the base of silicon planar uncooled detector and CsI(Tl) scintillator. The device is designed for interoperative and extraoperative search for differences in the concentration of radiopharmaceuticals in the energy range from 100 to 360 keV. Test stand was developed for determining the angular resolution of the gamma probe. На базі кремнієвого планарного неохолоджуваного детектора і сцинтилятора СsI(Tl) розроблений портативний гамма-зонд з автономним живленням. Прилад розрахований на інтероперативний та екстраоперативний пошуки відмінностей у концентрації радіофармацевтичних препаратів у енергетичному діапазоні 100 до 360 кеВ. Розроблено тестовий стенд для визначення кутового розподілу гамма-зонда.